Analysis of thermal performance of geophonic down-hole measuring tools; a numerical and experimental investigation. (5th June 2018) - Weerasinghe, Rohitha; Hughes, Thomas
Highlights: Computational fluid dynamics analysis of Peltier cooling of downhole tools. CFD analysis of the performance of Colsiblo and Nibron has been presented. A curve fitting technique best predicts thermal performance of Peltier cooling. Peltier cooling and CFD designs improve downhole tool performance up to 25 K. Abstract: Downhole tools encounter harsh environmental conditions due to pressure and elevated temperatures. Use of Peltier cooling in down-hole seismic tooling has been restricted by the performance of such devices at elevated temperatures. Present paper analyses the performance of Peltier cooling in temperatures suited for down-hole measuring equipment using measurements, predicted manufacturer data and computational fluid dynamic analysis. A critical analysis of Peltier performance prediction techniques is presented with measurements. Validity of the extrapolation of thermoelectric cooling performance at elevated temperatures has been tested using computational models for thermoelectric cooling device. This method has been used to model cooling characteristics of a prototype downhole tool and the computational technique used in has proven valid. Further, an CFD analysis of the performance of two heat sink metals has been presented. The experimental and modelling exercise was targeted at achieving cooling performance that would enable the tool withstand temperatures near 200 ° C.